Ameriacan Headway 1 : Workbook - Soars, Liz (Oxford University Press, 2009)
American Headway is a famous series for students to practice and improve English skills. Its proven methodology - focus on grammar, clear vocabulary syllabus, integrated skills work - gives you lessons that really work in class.